About Possibilities to Develop Educational Online Games With the Help Of Web Technologies - Mirabdullayev Ismoiljon Ibrahimjon ugli (International Journal on Human-Computing Studies, 2021)
This article describes the possibilities of web technology to develop educational online games for young children. It covers the technical possibilities of the virtual games "Counting Together" and "Find the Number I Thinked" designed by the author to form the first mathematical concepts in young children